Pozycja kobiet na rynku pracy w świetle regulacji Unii Europejskiej - BABIAK, Jerzy (Przegląd Politologiczny, 2018)
The position of women on the European labor market continues to be unstable. In order to make the opportunities for both genders equal at the EU level, appropriate regulations have been adopted since its beginnings. The first regulations focused on the issue of discrimination, aiming at a policy of anti-discrimination. The range of regulations in this area has gradually expanded to become an important part of EU policy. Any improvement in the situation is as- sessed in terms of increased competitiveness, innovativeness and economic growth. EU regulations and programs to promote gender equality, including those aimed at improving the situation of women on the labor market have now become a significant field of the Community’s activities. Progress there is already noticeable, although it continues to call for further commitment and cooperation on many levels.